ApoE (Apolipoprotein E) in Brain Pericytes Regulates Endothelial Function in an Isoform-Dependent Manner by Modulating Basement Membrane Components. Issue 1 (January 2020) - Yamazaki, Yu; Shinohara, Mitsuru; Yamazaki, Akari; Ren, Yingxue; Asmann, Yan W.; Kanekiyo, Takahisa; Bu, Guojun
Abstract : Objective: The ε4 allele of the APOE gene ( APOE4 ) is the strongest genetic risk factor for Alzheimer disease when compared with the common ε3 allele. Although there has been significant progress in understanding how apoE4 (apolipoprotein E4) drives amyloid pathology, its effects on amyloid-independent pathways, in particular cerebrovascular integrity and function, are less clear. Approach and Results: Here, we show that brain pericytes, the mural cells of the capillary walls, differentially modulate endothelial cell phenotype in an apoE isoform-dependent manner. Extracellular matrix protein induction, tube-like structure formation, and barrier formation were lower with endothelial cells cocultured with pericytes isolated from apoE4-targeted replacement (TR) mice compared with those from apoE3-TR mice. Importantly, aged apoE4-targeted replacement mice had decreased extracellular matrix protein expression and increased plasma protein leakages compared with apoE3-TR mice. Conclusions: ApoE4 impairs pericyte-mediated basement membrane formation, potentially contributing to the cerebrovascular effects of apoE4. Abstract : Supplemental Digital Content is available in the text.